Dhartiputras: The Tharus, Their Indigeneity, and the Effects of Modernity - Paudel, Shankar (KMC Research Journal, 2024)
The paper explores how modernity has affected the indigeneity of the Tharu people who have lived for years on the outskirts of the Chitwan National Park in Sauraha. Once their residence before the park was established, Chitwan National Park is mostly unreachable to them. This paper investigates the indigeneity of the Tharus living especially in and around Sauraha, Chitwan, with regard to their survival, which is mostly dependent on nature and natural entities. Furthermore, the paper also explores how the shifting ritus affect their way of life. Modernity has negatively impacted the Tharu people, therefore influencing not only their way of life but also their indigeneity. The main professions—farming, fishing, and tourism—they used to depend on have now been greatly influenced by the modern practices that have easily devalued their traditional practices. This study is carried out based on the interviews between 2017 and 2020 with some local Tharus and additional secondary sources that read Tharus as the Dhartiputras.